1998
DOI: 10.1080/02681219880000581
|View full text |Cite
|
Sign up to set email alerts
|

Molecular typing ofMalasseziaspecies with PFGE and RAPD

Abstract: The currently recognized seven species of Malassezia all have different karyotypes which do not vary intraspecifically, except in M. furfur which displayed two different karyotypes. In contrast, random amplified polymorphic DNA (RAPD) typing showed the presence of genetic variation in all species. It is concluded that karyotype analysis is useful for species identification, and RAPD typing can be used in epidemiological investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
59
1
14

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 34 publications
8
59
1
14
Order By: Relevance
“…Recently, data from several institutions have suggested that M. globosa is associated with pityriasis versicolor (19,20), that M. restricta is associated with seborrheic dermatitis (24,29), and that M. furfur infections have been observed in hospitalized neonates with very low birth weight receiving intravenous lipid emulsions (2,3,4,7,23,28). In agreement with these reports, we isolated mainly M. globosa from pityriasis versicolor and M. restricta from seborrheic dermatitis in the present study.…”
Section: Discussionsupporting
confidence: 81%
“…Recently, data from several institutions have suggested that M. globosa is associated with pityriasis versicolor (19,20), that M. restricta is associated with seborrheic dermatitis (24,29), and that M. furfur infections have been observed in hospitalized neonates with very low birth weight receiving intravenous lipid emulsions (2,3,4,7,23,28). In agreement with these reports, we isolated mainly M. globosa from pityriasis versicolor and M. restricta from seborrheic dermatitis in the present study.…”
Section: Discussionsupporting
confidence: 81%
“…Indeed, colonies of this species vary in size and form and show a high degree of cellular pleomorphism, including oval, cylindrical, and spherical cells (18,22). Techniques such as randomly amplified polymorphic DNA and amplified fragment length polymorphism have demonstrated high intraspecific variability in this species (2,5,44). The atypical assimilation pattern of our isolates, involving an inability to utilize Tween 20, 40, or 60, reveals a metabolic variation probably resulting from alternate gene expression.…”
Section: Discussionmentioning
confidence: 96%
“…The DNA relatedness of the isolates was based on RAPD and AFLP analyses. The RAPD analysis used primers M13, GTG5, OPA2, and OPA4, as described by Boekhout et al (5). The patterns of the individual primers were compared and summarized in one overall classification scheme.…”
Section: Methodsmentioning
confidence: 99%